2003
DOI: 10.1016/s1386-1425(03)00015-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photostability of ICG in close proximity to gold colloids

Abstract: Photobleaching of fluorophores frequently limits their detectability or observation time. We examined Indocyanine green (ICG) which is widely used in medical testing and is highly unstable. We showed that spatial localization of ICG near metallic gold colloids resulted in increased photostability. This suggests the use of fluorophore-metal conjugates in situations adversely affected by photobleaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 31 publications
(38 reference statements)
2
40
0
Order By: Relevance
“…Silver nanostructures, used in recent studies for metal-enhanced fluorescence, 13,14,[17][18][19][20][21][22][23][24][25][26]29,34 show blinking that is dependent on both the type of structure studied and irradiance of the illumination source. We typically observed that silver fractal-like structures could readily be made luminescent with irradiances of 30 W/cm 2 or more, as compared to silver island films, which required at least a 3-5-fold increase, >100 W/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver nanostructures, used in recent studies for metal-enhanced fluorescence, 13,14,[17][18][19][20][21][22][23][24][25][26]29,34 show blinking that is dependent on both the type of structure studied and irradiance of the illumination source. We typically observed that silver fractal-like structures could readily be made luminescent with irradiances of 30 W/cm 2 or more, as compared to silver island films, which required at least a 3-5-fold increase, >100 W/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to studying their luminescent blinking properties for potential applications as luminescent probes, as markers, and for medical imaging, our primary interest lies in their interactions with organic fluorophores, and how they modify fluorophore spectral properties. The favorable effects produced by close proximity fluorophores to metallic nanostructures includes increased quantum yields and reduced lifetimes, 13,14,17,18 increased fluorophore photostability, 13,14,19,20 enhanced multiphoton excitation, 21,22 and modified rates of energy transfer. [23][24][25] These interactions have been described as due to changes in the photonic mode density, PMD, around the fluorophore,26 and are considered to be through-space as compared to SERS, which is widely thought to be a contact interaction.27 , 28 Such effects are not normally observed in bulk media, where the photonic mode density is not that different from a vacuum, but can be changed by close proximity silver nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are due to the interactions of the excited-state fluorophores with the surface plasmon resonances on the surface of the metal [14][15][16][17]. These interactions can result in increased rates of excitation, increased intensities (quantum yields), and even quenching [18]. For our applications of enhanced fluorescence/luminescence and therefore luminophore detectability, the most important effect is an increase in the radiative decay rate of fluorophores, , which occurs for fluorophores positioned ≈50-200Å from the metallic surface [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…In this short note, we show that 3-to 5-fold enhanced fluorescence signals can be obtained from SiO 2 -coated silver colloids labeled with Cy3 and by their aggregation in suspension. This inert coating alleviates the close proximity quenching by noble-metals [1,9], as well as provides for a wide variety of chemistries for biomolecule attachment.The preparation of silica-coated silver spheres and biotinylation of the silica coated silver spheres in suspension is performed in multiple steps. Firstly, the silver spheres were prepared in solution.…”
mentioning
confidence: 99%
“…This inert coating alleviates the close proximity quenching by noble-metals [1,9], as well as provides for a wide variety of chemistries for biomolecule attachment.…”
mentioning
confidence: 99%